1994
DOI: 10.1200/jco.1994.12.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Use of granulocyte colony-stimulating factor before, during, and after fludarabine plus cytarabine induction therapy of newly diagnosed acute myelogenous leukemia or myelodysplastic syndromes: comparison with fludarabine plus cytarabine without granulocyte colony-stimulating factor.

Abstract: On average, G-CSF before, during, and after FA had no effect on CR or infection rates in this population, in which elderly patients and poor prognostic factors were prevalent. The use of FA and laminar airflow rooms rather than more usual therapy needs to be considered when analyzing the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
144
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(149 citation statements)
references
References 17 publications
3
144
0
2
Order By: Relevance
“…Since 1999, guidelines for trimethoprim -sulphamethoxazole (TMP -SMX) prophylaxis have been utilised in patients receiving selected high-intensity chemotherapy protocols: hyper-CVAD (Kantarjian et al, 2000), VAD (Barlogie et al, 1984), CEVAD and FLAG (Estey et al, 1994). Adherence to the guidelines and frequency of chemoprophylaxis in other patients with haematological malignancy or solid tumours is unknown.…”
mentioning
confidence: 99%
“…Since 1999, guidelines for trimethoprim -sulphamethoxazole (TMP -SMX) prophylaxis have been utilised in patients receiving selected high-intensity chemotherapy protocols: hyper-CVAD (Kantarjian et al, 2000), VAD (Barlogie et al, 1984), CEVAD and FLAG (Estey et al, 1994). Adherence to the guidelines and frequency of chemoprophylaxis in other patients with haematological malignancy or solid tumours is unknown.…”
mentioning
confidence: 99%
“…The fludarabine, high-dose cytarabine and idarubicin combination regimen, often referred to as FLAG-Ida or FAI, was developed and piloted at MD Anderson Cancer Center [78][79][80] based on the preclinical studies of Plunkett et al [81,82]. Following the encouraging results, the MRC AML 15 trial compared, in a randomized study of younger patients with AML, FLAG-Ida to 3 1 7 regimens with etoposide.…”
Section: Younger Patients With Amlmentioning
confidence: 99%
“…[9][10][11] In this context, several reports have shown the efficacy of the combination of G-CSF with cell-cycle-specific chemotherapeutic agents such as cytarabine in refractory myeloid malignancies. [12][13][14][15] In a randomized trial, it has been shown that addition of G-CSF to cytarabine-based induction chemotherapy for AML patients significantly contributes to a higher rate of disease-free survival owing to the reduced rate of relapse. 15 In an HSCT setting, we previously reported the results of 14 patients in two institutes, who underwent allogeneic HSCT from an HLA-identical sibling after being conditioned with TBI and G-CSF-combined high-dose cytarabine; in these cases, a high disease-free survival rate of 67.7% was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] As granulocyte colony-stimulating factor (G-CSF) has been shown to increase the susceptibility of some myeloid leukemia cells to cytarabine in vitro, [9][10][11] it has been used clinically in combination with cytarabine for refractory acute myelogenous leukemia (AML) or MDS. [12][13][14][15] In our previous report, G-CSF was administered simultaneously with high-dose cytarabine as part of the conditioning regimen for advanced MDS based on these findings, and the 5-year overall survival rate of 14 patients was 75.5% with only one case of disease relapse. 16 The present study, which is a single institute evaluation of more patients, including HSCT recipients from alternative donors, examined the efficacy and safety of a G-CSFcombined high-dose cytarabine regimen for advanced MDS.…”
Section: Introductionmentioning
confidence: 99%